Mobilizing Investors for Blue Growth - van den Burg, Sander W. K.; Stuiver, Marian; Bolman, Bas C.; Wijnen, Roland; Selnes, Trond; Dalton, Gordon (Frontiers in Marine Science, 2017)
The European Union’s Blue Growth Strategy is a long term strategy to support sustainable growth in the marine and maritime sectors, aiming to contribute to innovation and economic growth (European Commission, 2012). The EU sees the financial sector as a key partner to bring about transition to sustainable consumption and production. However, knowledge about investment behaviour, experience with working with these investors and ways to engage investors in the Blue Growth sectors is lacking. This paper examines this knowledge gap. It characterizes investors and identifies investor behaviour, investors’ motives and conditions and criteria relevant for investors to invest in Blue Growth sectors. The presented results are derived from a literature study on investors and investment behaviour, an electronic survey and in-depth interviews. Stereotypical images of private equity bankers or wealthy individuals do not do justice to the diversity of investors involved in the Blue Growth sectors. These sectors are still in development and various risks reduce the willingness to invest. Risk mitigation should be seen as a shared responsibility of entrepreneurs, investors and governments. Government support must go further than financial support for research and development or technological demonstration projects. Proven technologies get stuck in the Valley of Death as investors alone are not willing to take the risk associated with upscaling of promising technologies. Tied in a reciprocal relationship, governments need to attract private investors – their capital, knowledge and networks – to further grow of the Blue Growth sectors while investors need stable, predictable and effective government support schemes to mitigate their financial risks.